2020
DOI: 10.1097/qai.0000000000002452
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Retrospective Evaluation on the Efficacy of Lopinavir/Ritonavir and Chloroquine to Treat Nonsevere COVID-19 Patients

Abstract: Background: The effectiveness of lopinavir/ritonavir (LPV/r) and chloroquine treatment for COVID-19 has not been verified. Methods: We conducted a retrospective study to summarize the clinical practices of nonsevere patients with COVID-19 receiving the standard care, LPV/r or chloroquine in Beijing Ditan Hospital from January 20 to March 26, 2020. The main outcome measurements include the changes of cycle threshold values of open reading frame 1 ab (ORF1ab) and nucleocapsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…Although some evidence with positive results early appeared, most of these studies are now considered of insufficient quality, limited, and mostly affected by high risks of bias (Gautret et al 2020 ; Hernandez et al 2020 ; Huang et al 2020 ; Rosendaal 2020 ; Wang et al 2020 ). Nowadays, there are increasing data reporting evidence of the ineffectiveness of CQ and HCQ in improving the prognosis or shorten the clinical course of COVID-19 (Gao et al 2020a ; Horby et al 2020 ; Kashour et al 2020 ; Lammers et al 2020 ). Also, some reports highlight the severe risks, including death, when CQ is used in high dose and the potentially detrimental consequences of rapid dissemination of over-interpreted data of its efficacy (Das et al 2020 ; Ektorp 2020 ; Kim et al 2020 ; Touret and de Lamballerie 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although some evidence with positive results early appeared, most of these studies are now considered of insufficient quality, limited, and mostly affected by high risks of bias (Gautret et al 2020 ; Hernandez et al 2020 ; Huang et al 2020 ; Rosendaal 2020 ; Wang et al 2020 ). Nowadays, there are increasing data reporting evidence of the ineffectiveness of CQ and HCQ in improving the prognosis or shorten the clinical course of COVID-19 (Gao et al 2020a ; Horby et al 2020 ; Kashour et al 2020 ; Lammers et al 2020 ). Also, some reports highlight the severe risks, including death, when CQ is used in high dose and the potentially detrimental consequences of rapid dissemination of over-interpreted data of its efficacy (Das et al 2020 ; Ektorp 2020 ; Kim et al 2020 ; Touret and de Lamballerie 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning of the outbreak in Arequipa (March-April 2020), Hydroxychloroquine with or without lopinavir / ritonavir or azithromycin was used as a standard treatment and according to the best evidence at that time as a therapy against SARS-CoV-2 according to national guidelines [1] and the medical literature available [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Data from observational studies revealed no differences between lopinavir/ritonavir and hydroxychloroquine administered in patients with severe or mild-moderate COVID-19 (Choi et al, 2020;Karolyi et al, 2020;Lecronier et al, 2020). A retrospective study, conducted instead in non-severe patients with COVID-19, also showed no improvement in the prognosis or shortening of clinical course with lopinavir/ritonavir treatment (Gao et al, 2020). On the contrary, a retrospective cohort study showed that the combined antiviral therapy (lopinavir/ritonavir plus umifenovir) is more effective than lopinavir/ritonavir monotherapy (Deng et al, 2020).…”
Section: Clinical Evidence Of Antiviral Agentsmentioning
confidence: 94%